"You gotta try it all": Parents' Experiences with Robotic Gait Training for their Children with Cerebral Palsy. (2nd October 2015) - Beveridge, Briony; Feltracco, Deanna; Struyf, Jillian; Strauss, Emily; Dang, Saniya; Phelan, Shanon; Wright, F. Virginia; Gibson, Barbara E.
ABSTRACT: Aims: Innovative robotic technologies hold strong promise for improving walking abilities of children with cerebral palsy (CP), but may create expectations for parents pursuing the "newest thing" in treatment. The aim of this qualitative study was to explore parents' values about walking in relation to their experiences with robotic gait training for their children. Methods: Semi-structured interviews were conducted with parents of five ambulatory children with CP participating in a randomized trial investigating robotic gait training effectiveness. Results: Parents valued walking, especially "correct" walking, as a key component of their children's present and future well-being. They continually sought the "next best thing" in therapy and viewed the robotic gait trainer as a potentially revolutionary technology despite mixed experiences. Conclusions : The results can help inform rehabilitation therapists' knowledge of parents' values and perspectives, and guide effective collaborations toward meeting the therapeutic needs of children with CP.